Open Questions in Cosmic-Ray Research at Ultrahigh Energies - Alves Batista, Rafael; Biteau, Jonathan; Bustamante, Mauricio; Dolag, Klaus; Engel, Ralph; Fang, Ke; Kampert, Karl-Heinz; Kostunin, Dmitriy; Mostafa, Miguel; Murase, Kohta; Oikonomou, Foteini; Olinto, Angela V.; et al. (Frontiers in Astronomy and Space Sciences, 2019)
We review open questions and prospects for progress in ultrahigh-energy cosmicray (UHECR) research, based on a series of discussions that took place during the “The High-Energy Universe: Gamma-Ray, Neutrino, and Cosmic-ray Astronomy” MIAPP workshop in 2018.Specifically, we overview open questions on the origin of the bulk of UHECRs, the UHECR mass composition, the origin of the end of the cosmic-ray spectrum, the transition from Galactic to extragalactic cosmic-rays, the effect of magnetic fields on thetrajectories of UHECRs, anisotropy expectations for specific astrophysical scenarios, hadronicinteractions, and prospects for discovering neutral particles as well as new physics at ultrahighenergies. We also briefly overview upcoming and proposed UHECR experiments and discusstheir projected science reach.